Long-term neurocognitive function after whole-brain radiotherapy in patients with melanoma brain metastases in the era of immunotherapy - Salzmann, Martin; Hess, Klaus; Uzun-Lang, Kristin; Enk, Alexander; Jordan, Berit; Hassel, Jessica C. (Strahlentherapie und Onkologie, 2022)
Whole-brain radiotherapy (WBRT) used to be standard of care for patients suffering from melanoma brain metastases (MBM) and may still be applicable in selected cases. Deterioration of neurocognitive function (NCF) is commonly seen during and after WBRT. Knowledge on long-term effects in melanoma patients is limited due to short survival rates. With the introduction of immune checkpoint inhibitors, patients may experience ongoing disease control, emphasizing the need for paying more attention to potential long-term adverse effects.
Gesehen am 17.11.2022